A Compact Structure of Cytochrome c Trapped in a Lysine-Ligated State: Loop Refolding and Functional Implications of a Conformational Switch - Amacher, Jeanine F. (J Am Chem Soc, 2015)
It has been suggested that the alkaline form of cytochrome c (cyt c) regulates function of this protein as an electron carrier in oxidative phosphorylation and as a peroxidase that reacts with cardiolipin (CL) during apoptosis. In this form, Met80, the native ligand to the heme iron, is replaced by a Lys. While it has become clear that the structure of cyt c changes, the extent and sequence of conformational rearrangements associated with this ligand replacement remain a subject of debate. Herein we report a high-resolution crystal structure of a Lys73-ligated cyt c conformation that reveals intricate change in the heme environment upon this switch in the heme iron ligation. The structure is surprisingly compact, and the heme coordination loop refolds into a β-hairpin with a turn formed by the highly conserved residues Pro76 and Gly77. Repositioning of residue 78 modifies the intraprotein hydrogen-bonding network and, together with adjustments of residues 52 and 74, increases the volume of the heme pocket to allow for insertion of one of the CL acyl moieties next to Asn52. Derivatization of Cys78 with maleimide creates a solution mimic of the Lys-ligated cyt c that has enhanced peroxidase activity, adding support for a role of the Lys-ligated cyt c in the apoptotic mechanism. Experiments with the heme peptide microperoxidase-8 and engineered model proteins provide a thermodynamic rationale for the switch to Lys ligation upon perturbations in the protein scaffold.